Organizational Culture and Work Motivation Predict Teacher Performance Through Management Information Systems - Ardiansyah, Dhinar Mahardika; Suryaningyas, Dianawati; Sedyastuti, Kristina (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2026)
This study examined how organizational culture and work motivation influence teacher performance at SMA Negeri 1 Bululawang, Malang Regency, with management information systems (MIS) positioned as an intervening variable. The problem addressed is the persistence of uneven teacher performance despite the existence of a supportive school culture, relatively strong work motivation, and administrative-digital systems that are expected to improve professional work. The main research gap addressed in this study concerns the limited explanation of how organizational values and teacher motivation are translated into measurable performance through a digital management mechanism. Therefore, MIS is positioned not merely as a technical predictor, but as a mediating mechanism that links organizational and motivational factors to teacher performance. An explanatory quantitative design was employed. From a population of 80 school personnel, 60 respondents were selected through purposive sampling followed by total sampling of eligible participants. Data were collected using a Likert-scale questionnaire covering teacher performance, organizational culture, work motivation, and MIS use. The model was analyzed using Partial Least Squares structural equation modeling with WarpPLS 8.0. The findings show that organizational culture significantly predicted MIS use (β = 0.611, p < .001), work motivation significantly predicted MIS use (β = 0.205, p = .047), work motivation directly predicted teacher performance (β = 0.469, p < .001), and MIS significantly predicted teacher performance (β = 0.332, p = .003). Organizational culture did not directly predict performance (β = -0.045, p = .362), but it had a significant indirect effect through MIS (β = 0.203, p = .010). Conversely, the indirect effect of work motivation through MIS was not significant. These results suggest that digital management systems serve as a bridge through which organizational culture becomes performance-relevant, particularly when implementation is consistent, data-driven, and supported by digital capacity building.